2015
DOI: 10.1098/rspb.2015.1453
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted seasonal biology impacts health, food security and ecosystems

Abstract: The rhythm of life on earth is shaped by seasonal changes in the environment. Plants and animals show profound annual cycles in physiology, health, morphology, behaviour and demography in response to environmental cues. Seasonal biology impacts ecosystems and agriculture, with consequences for humans and biodiversity. Human populations show robust annual rhythms in health and well-being, and the birth month can have lasting effects that persist throughout life. This review emphasizes the need for a better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
119
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 115 publications
(171 reference statements)
1
119
0
3
Order By: Relevance
“…Our present data open new possibilities for extensive global analyses, which could disentangle contributions of different seasonal drivers to a broad range of infectious diseases. There is a pressing need for such knowledge because global seasonality is becoming rapidly modified and disrupted through human action, with potentially far-reaching implications for infectious disease transmission (45).…”
Section: Discussionmentioning
confidence: 99%
“…Our present data open new possibilities for extensive global analyses, which could disentangle contributions of different seasonal drivers to a broad range of infectious diseases. There is a pressing need for such knowledge because global seasonality is becoming rapidly modified and disrupted through human action, with potentially far-reaching implications for infectious disease transmission (45).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the complete ZIKV genome was 23 recovered from the brain of a fetus with microcephaly aborted by an expectant mother 24 infected during the 13 th week of gestation [7], and the CDC reported on two newborns 25 from Brazil with microcephaly who died shortly after birth and two miscarriages, all 26 tested positive for ZIKV [8]. In addition to the epidemiological evidence, newly 27 developed mouse models of ZIKV have demonstrated that ZIKV strains from French…”
mentioning
confidence: 99%
“…Although infectious diseases are seasonal, the timing of the high-transmission season can 80 (1) vary among pathogens within a country and (2) vary among countries/regions for a 81 given pathogen [27]. The drivers of DENV, WNV, YFV, and CHIKV seasonality are transmssion-relevant contact rate among hosts/vectors, the density of hosts, and vector 87 abundance [16,21,27].…”
mentioning
confidence: 99%
See 2 more Smart Citations